Implementasi Terapi Muhasabah Sebagai Upaya Memelihara Kesehatan Mental Dalam Usaha Penanggulangan Adiksi Narkoba (Studi Lapangan Lapas Narkotika Cirebon) - Yumna Yumna; Ginanjar Kusuma Wardana; Hanif Fauziah; Muslikhin Muslikhin; Salsabila Syahla Bachtiar; Ega Novitasari (Syifa al-Qulub, 2021)
In this particular modern life, we feel great advances in science and technology. These advances have been able to make it easier for us. All advances in these various fields are not free from deterioritation, one of which is in humans themselves such as pressure due to work or family that cause such as addictions on Narcotics which create psychological pressure on humans and mental disorders. This gets attention of academics to examine the cause and try to find a solution to this problem. Then the concept of Mental Health Care was created. Healthy mental standardization is very complex and varied because this is the result of human thinking with various methods, approaches and epistemology that are different from each researcher. Therefore, it creates to a different standardization of healthy mental health. And we also have different criteria and methods of mental health care. One method of Mental Health Care according to Islam is to use the Sufistic Psychotherapy method in which there are various kinds of therapy and one of them is muhasabah therapy. Muhasabah according to some tarikat practitioners and Sufis meansthat muhasabah is the process of examining ourselves on all the actions we have done from our early days remembering to the present condition starting from thoughts or deeds assessing deeds to determine the quality of ourselves before Allah SWT or self-analyze. This paper is expected to be able to provide awareness to readers about the dangers of the effects of narcotics on the mental health of its users and the importance of maintaining mental health according to an Islamic perspective and provide some solutions through muhasabah therapy that can be applied to these problems.